Natural Products Targeting Liver X Receptors or Farnesoid X Receptor - She, Jianglian; Gu, Tanwei; Pang, Xiaoyan; Liu, Yonghong; Tang, Lan; Zhou, Xuefeng (Frontiers in Pharmacology, 2022)
Nuclear receptors (NRs) are a superfamily of transcription factors induced by ligands, also function as integrators of hormonal and nutritional signals. Among NRs, the liver X receptors (LXRs) and farnesoid X receptor (FXR) have been of significance as targets for the treatment of metabolic syndrome-related diseases. In recent years, natural products targeting LXRs and FXR have received remarkable interests as a valuable source of novel ligands encompassing diverse chemical structures and bioactive properties. This review aims to survey natural products, originating from terrestrial plants and microorganisms, marine organisms, and marine-derived microorganisms, which could influence LXRs and FXR. In recent two decades (2000-2020), 261 natural products were discovered from natural resources as LXRs/FXR modulators, 109 agonists and 38 antagonists targeting LXRs, while 72 agonists and 55 antagonists targeting FXR. The docking evaluation of desired natural products targeted LXRs/FXR is finally discussed. This comprehensive overview will provide a reference for future study of novel LXRs and FXR agonists and antagonists to target human diseases and attract an increasing number of professional scholars majoring in pharmacy and biology more in-depth discussion.